Systematic review and meta-analysis on the proportion of patients with breast cancer who develop bone metastases. (July 2017) - Body, Jean-Jacques; Quinn, Geoffrey; Talbot, Susan; Booth, Emma; Demonty, Gaston; Taylor, Aliki; Amelio, Justyna
Highlights: Systematic review and meta-analysis of bone metastases in those with breast cancer. Included data from more than 175, 000 patients with breast cancer. 12% of patients with stage I–III breast cancer developed bone metastases. Of those who developed any metastases during follow-up, 55% had bone metastases. Of patients with metastatic breast cancer at study start, 58% had bone metastases. Abstract: A systematic literature review was conducted to quantify populations of patients with primary breast cancer in whom bone metastases were detected at study start or during follow-up. Searches were performed in PubMed and EMBASE using terms related to breast cancer and bone metastases. Articles had to have been published 01/01/99–31/12/13, and to report data on the proportion of patients with bone metastases among patients with breast cancer. In total, 156 articles were included in the meta-analysis. A median of 12% of patients with stage I–III breast cancer developed bone metastases during a median follow-up of 60 months. Of patients who developed metastatic disease during follow-up, 55% (median) had bone metastases. Of those with metastatic breast cancer at study start, 58% (median) had bone metastases. These data help to inform on the global burden of bone metastases by defining patient populations that are at risk of developing bone metastases.